KONTEKSTUALISASI SEBAGAI LANDASAN STRATEGIS PELAKSANAAN MISI: PENDEKATAN TEORI DAN PENERAPAN - Arianus Lase; Yakub Hendrawan Perangin Angin (Student Evangelical Journal Aiming At Theological Interpretation, 2026)
Contextualization is a critical approach in missiology that ensures the Gospel message remains relevant to local cultures without compromising its core truth. This research examines contextualization as a strategic foundation for mission implementation through both theoretical and practical approaches. By analyzing theological principles, contextualization models, and field case studies particularly within the context of increasingly developing urban societies this study demonstrates that effective contextualization requires a balance between faithfulness to Scripture and sensitivity to socio-cultural contexts. Therefore, the outcome of this entire process affirms that contextualization can no longer be viewed merely as a method or ministry technique. Rather, it has evolved into a transformative mission paradigm that fundamentally reframes the understanding, strategy, and practice of mission itself.